Impact of Cardiac Rehabilitation versus Standard Care in Reducing Mortality and Hospitalization in Post-Myocardial Infarction Patients: A Systematic Review and Meta-Analysis - Patel, Rutvij; Mahmood, Arhum; Virk, Ghazala S.; Sharma, Sital; Gundoji, Chethan Raj; Sadam, Sreeja; Ahmed, Zubair; Naz, Falak; Mirza, Muhammad Sohail S.; Essani, Binish; et al. (Cardiology and Cardiovascular Medicine, 2025)
Cardiovascular disease is the major death cause in worldwide and a very high on the list of causes for recurrent cardiac events and hospitalization for myocardial infarction (MI) survivors. Cardiac rehabilitation (CR) is a multidisciplinary intervention planned to enhance the recovery and longterm outcomes. However, it is reported variably on mortality and hospital readmissions due to its effect. This systematic review and meta-analysis give a detail account of CR versus standard care in terms of performing a decimating role on both mortality and hospital admissions for post-MI patients. It was published from 2000 to 2025 and published on randomized controlled trials (RCTs) investigating structured CR interventions against standard post-MI care and mortality or hospitalization outcomes. The pooled analysis revealed that CR participation was linked with a wide 28% reduction in the all-cause mortality (r= 0.72; 95% confidence interval [CI] 0.58–0.89) and a 25% reduction in hospitalization rates (r= 0.75; 95% CI 0.62–0.91) compared to standard care. Traditional exercise-based CR programs consistently showed survival benefits, while family-centered and psychosocially focused models demonstrated additional improvements in long-term outcomes. Despite these positive effects, substantial heterogeneity was observed (I² > 90%), reflecting differences in intervention duration, intensity, patient demographics, and follow-up periods. Most researches showed moderate to low hazards of bias, enhancing confidence in the results. This review confirms the vital role of cardiac rehabilitation as a key secondary prevention strategy post-MI, significantly reduction in clinical outcomes and reducing healthcare burden. However, more research is required to optimize CR protocols, particularly for elderly and multimorbid patients, and to integrate mental health support effectively. Embracing personalized and technology-enabled CR may further enhance patient engagement and benefits.